2015
DOI: 10.1515/chem-2015-0141
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of oligonucleotides by liquid chromatography with alkylamide stationary phase

Abstract: Abstract:The main aim of the present investigation was to determine retention behavior and interactions of oligonucleotides with alkylamide stationary phase. Five oligonucleotides, differing in the sequence, were tested. Changes in the composition of the mobile phase, i.e. pH (5.0−7.0) and buffer concentration (30−75 mM) were investigated in detail. In addition, the hydrophobic and electrostatic parameters were measured for the different pH's and salt concentrations. The theoretical model of interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The alkylamide stationary phase was also applied to OGN studies in RP HPLC and IPC [ 57 , 73 ]. Compared to C18, the retention of OGNs was lower [ 56 , 63 ].…”
Section: Application Of Adsorbents With Different Modifications For S...mentioning
confidence: 99%
See 2 more Smart Citations
“…The alkylamide stationary phase was also applied to OGN studies in RP HPLC and IPC [ 57 , 73 ]. Compared to C18, the retention of OGNs was lower [ 56 , 63 ].…”
Section: Application Of Adsorbents With Different Modifications For S...mentioning
confidence: 99%
“…The polar heteroatoms implemented in alkyl chains (e.g., in the amide group) increase the polarity of the stationary phase and, at the same time, reduced the retention of OGNs ( Figure 4 ) [ 53 , 57 , 64 ]. It was also shown that OGN retention increases with the decrease of the mobile phase pH in RP mode, indicating the critical role of surface charge change [ 73 ]. The advantage of the alkylamide stationary phase is that the application of RP HPLC allowed for the successful separation of sequence isomers at acidic pH containing a high concentration of buffer.…”
Section: Application Of Adsorbents With Different Modifications For S...mentioning
confidence: 99%
See 1 more Smart Citation
“…24 In an HPLC column, the surface of the adsorbents is modified by various functional groups, such as amino propyl 25 and amide groups. 26 Although many adsorbents have been developed for effective separation and purification, efficient separation conditions (pH, organic solvent ratio, and functional group) must be investigated through trial and error. Therefore, a theoretical explanation of the DNA separation mechanism is essential for further chromatographic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…pH of the mobile phase also plays an important role to control retention and selectivity. For example, in the case of alkylamide stationary phases, as reported in Ref [110],. when pH is buffered at 6 or 7, the negative charges on the stationary phase are not efficiently shielded by the salts.…”
mentioning
confidence: 99%